Approximating bone ECM: Crosslinking directs individual and coupled osteoblast/osteoclast behavior. (October 2016) - Hwang, Mintai P.; Subbiah, Ramesh; Kim, In Gul; Lee, Kyung Eun; Park, Jimin; Kim, Sang Heon; Park, Kwideok
Abstract: Osteoblast and osteoclast communication ( i.e. osteocoupling) is an intricate process, in which the biophysical profile of bone ECM is an aggregate product of their activities. While the effect of microenvironmental cues on osteoblast and osteoclast maturation has been resolved into individual variables ( e.g. stiffness or topography), a single cue can be limited with regards to reflecting the full biophysical scope of natural bone ECM. Additionally, the natural modulation of bone ECM, which involves collagenous fibril and elastin crosslinking via lysyl oxidase, has yet to be reflected in current synthetic platforms. Here, we move beyond traditional substrates and use cell-derived ECM to examine individual and coupled osteoblast and osteoclast behavior on a physiological platform. Specifically, preosteoblast-derived ECM is crosslinked with genipin, a biocompatible crosslinker, to emulate physiological lysyl oxidase-mediated ECM crosslinking. We demonstrate that different concentrations of genipin yield changes to ECM density, stiffness, and roughness while retaining biocompatibility. By approximating various bone ECM profiles, we examine how individual and coupled osteoblast and osteoclast behavior are affected. Ultimately, we demonstrate an increase in osteoblast and osteoclast differentiation on compact and loose ECM, respectively, and identify ECM crosslinking density as an underlying force in osteocoupling behavior. Graphical abstract: